Emergency Oral Contraceptive Consultations in Pharmacies in a Rural Setting: An Epidemiological Analysis. (April 2022) - Pearce, Emma; Jolly, Kate
Background: Emergency contraception has been available in pharmacies across England since 2001.There is a paucity of evidence describing those women accessing the service, particularly in rural locations, where pharmacies are integral to improving healthcare accessibility. Methods: Routinely collected data from all pharmacy consultations for emergency contraception in Shropshire, England, were obtained and anonymized for the study period April 1, 2016 to January 31, 2019. Consultations were described by time, age of consultee, rationale for consultation, method dispensed (levonorgestrel or ulipristal acetate), referral for copper intrauterine device fitting, chlamydia screening where appropriate and reason for choosing pharmacy setting. Repeat attenders were also described separately. Results: 3499 consultations occurred during the study period; 39% were aged between 16-20 years, and 52% attended following unprotected sexual intercourse. Levonorgestrel was initially most prescribed, however ulipristal acetate overtook it in 2018. Onward referral for copper intrauterine device and age-appropriate chlamydia screening took place in 3% and 4% of the eligible populations respectively. Women overwhelmingly chose the pharmacy setting owing to its convenience. Repeat attenders tended to be younger than single attenders, but otherwise similar. Conclusion: Pharmacy-based emergency contraception is an important and well-utilized service in this rural location and continued funding and possible service expansion should be considered.